Konsep Epistemologi Bayani, Irfani dan Burhani dalam Filsafat Pendidikan Islam - Marjuki, Sulton Nur Falaq; Nada, Zakiya Qothrun; Haq, Muhammad Izul; El-Yunusi, Muhammad Yusron Maulana (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2024)
Bayani's epistemological concept also emphasizes understanding texts and traditions, with the Koran and hadith as the main sources of knowledge. Irfani focuses on discovering the mystical aspects of knowledge and personal experience, while Burhani emphasizes rationality and logical reasoning, providing inspiration for the concept of this type of Islamic education, while Bayani and Irfani into the overall process and approach. Burhani elements examine This integration provides students with the benefit of a comprehensive and in-depth understanding of Islam while fostering the development of critical and analytical thinking skills. The importance of these concepts is that Islamic education requires a holistic approach that includes elements of Bayani, Irfani and Burhani in the learning process. This integration allows students to simultaneously gain a comprehensive and in-depth understanding of Islam and foster the development of critical and analytical thinking skills. This article makes an important contribution to understanding the theory and practice of Islamic education through the study of fundamental epistemological concepts. The practical implications of this research will help develop more effective curricula and teaching methods in the context of Islamic education. Keywords: Education, Epistemologi, Islam Â Abstrak Konsep epistemologis Bayani juga menekankan pada pemahaman teks dan tradisi, dengan al-Qur'an dan hadis sebagai sumber utama ilmu pengetahuan. Irfani berfokus pada penemuan aspek mistik pengetahuan dan pengalaman pribadi, sedangkan Burhani menekankan pada rasionalitas dan penalaran logis, memberikan inspirasi bagi konsep pendidikan Islam jenis ini, sedangkan Bayani dan Irfani ke dalam keseluruhan proses dan pendekatan. unsur Burhani memeriksa Integrasi ini memberikan siswa manfaat pemahaman Islam yang komprehensif dan mendalam sekaligus menumbuhkan pengembangan keterampilan berpikir kritis dan analitis. Pentingnya konsep-konsep tersebut Pendidikan Islam memerlukan pendekatan holistik yang memasukkan unsur Bayani, Irfani dan Burhani dalam proses pembelajaran. Integrasi ini memungkinkan siswa secara bersamaan memperoleh pemahaman Islam yang komprehensif dan mendalam serta menumbuhkan pengembangan kemampuan berpikir kritis dan analitis.Artikel ini memberikan kontribusi penting dalam memahami teori dan praktik pendidikan Islam melalui kajian konsep-konsep epistemologis mendasar. Implikasi praktis dari penelitian ini akan membantu mengembangkan kurikulum dan metode pengajaran yang lebih efektif dalam konteks pendidikan Islam. Kata Kunci: Pendidikan, Epistemologi, Islam